GUIDED SELF-HELP IN THE TREATMENT OF COMMON MENTAL HEALTH DISORDERS – THE DEVELOPMENT OF THE FINNISH GUIDED SELF-HELP (F-GSH) MODEL - KASPERI MIKKONEN, ALESSANDRA BOMBINO, ALEX VILLA, SARA NURMINEN, REETTA-MARIA ROIHA, PASI ROSLUND, JAN-HENRY STENBERG, JESPER EKELUND, SUOMA E. SAARNI, SAMULI SAARNI (Psychiatria Fennica)
ABSTRACT Increasing access to short-term, evidence-based psychological therapies in primary care or community-based settings is a key strategy for responding to the rapid increase of demand for mental health services seen in most Western countries. To succeed, it is necessary to maximize effectiveness and resource use by optimizing length, content, process, delivery format and use of technology in therapy. In Finland, guided self-help (GSH) has become one of the principal components of a modified stepped care system, aimed at improving access to treatment and maximizing the cost-effectiveness of the overall treatment system. Self-help (SH) and GSH therapy systems aim to optimize the use of trained therapists’ time while retaining the goals and effects of more conventional face-to-face therapies. By employing diverse digital solutions in treatment conceptualization and delivery, the access and flexibility of services can be enhanced. Unfortunately, the terminology and classifications describing: a) the different ways a therapist can interact with clients, and b) the augmentation of these interactions with various digital tools, have not kept pace with the advancements in new technologies. This significantly hinders scientific progress. In general, the effectiveness of SH and GSH for common mental health disorders, especially depression and anxiety, have been well demonstrated. In many cases, meta-analyses have shown no difference in effectiveness between GSH and other treatment formats. Further, SH seems to be superior to no treatment for depression and anxiety. This paper has two aims. First, to present a narrative literature review of meta-analytic evidence regarding SH and GSH, examining terminology and evidence base in both adult and youth services. Second, to describe the rationale, principles, development, key contents and implementation process of a national Finnish Guided Self-Help (F-GSH) service, developed as part of the Finnish First-line Therapies model.